2021
DOI: 10.3389/fpsyg.2021.750944
|View full text |Cite
|
Sign up to set email alerts
|

Olfaction in the Multisensory Processing of Faces: A Narrative Review of the Influence of Human Body Odors

Abstract: A recent body of research has emerged regarding the interactions between olfaction and other sensory channels to process social information. The current review examines the influence of body odors on face perception, a core component of human social cognition. First, we review studies reporting how body odors interact with the perception of invariant facial information (i.e., identity, sex, attractiveness, trustworthiness, and dominance). Although we mainly focus on the influence of body odors based on axillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 255 publications
(368 reference statements)
2
7
0
Order By: Relevance
“…Perception and behavioral effects of the acid fraction of human body odor remains poorly explored, compared to other families of compounds such as androstenes (in the field of face processing, see Damon et al, 2021). Here, we investigated whether HMHA, produced in larger proportions by men (Troccaz et al, 2009) could play a role in human interactions, either through intersexual processes (attraction) or intrasexual competition, which are two nonexclusive components of the sexual selection process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perception and behavioral effects of the acid fraction of human body odor remains poorly explored, compared to other families of compounds such as androstenes (in the field of face processing, see Damon et al, 2021). Here, we investigated whether HMHA, produced in larger proportions by men (Troccaz et al, 2009) could play a role in human interactions, either through intersexual processes (attraction) or intrasexual competition, which are two nonexclusive components of the sexual selection process.…”
Section: Discussionmentioning
confidence: 99%
“…However, the influence of (body) odors is likely to remain below the level of consciousness, without the odor being explicitly perceived (e.g., Richard Ortegón et al, 2022) and with possible disruption of the effect if the odor reaches conscious perception (Li et al, 2007). Additionally, whether the level of HMHA concentration used in the current study corresponds to the level naturally produced at the surface of the body is unknown, thus limiting the ecological validity of the approach (see discussion of this issue in Burke et al, 2012, and Damon et al, 2021). Third, the sample used in this study was rather small, which limits the generalizability and reliability of the conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that human mothers influence the hedonic polarity of their neonates’ initial olfactory responses and acquisition of food preference through their diet ( 52 ). OMP could thus participate in these early influences of general social cognition and therefore in the development of food preferences in humans ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Maternal odor could even be progressively dissociated from the perception of faces, as the proportion of faces in the infant's visual environment linearly decreases during the first year while the proportion of other body parts, especially hands, increases (Fausey et al, 2016). However, accumulating evidence shows that human odors are still associated with faces in adulthood (see Damon et al, 2021 for a recent review), indicating that body odor influence on face perception is not restricted to the maternal odor effect in the youngest infants.…”
Section: Olfactory-to-visual Facilitation Declines Gradually As a Fun...mentioning
confidence: 99%